2008
DOI: 10.2337/dc07-1870
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Cardiorespiratory Fitness and Risk of Type 2 Diabetes in Women

Abstract: OBJECTIVE -The purpose of this study was to determine the independent and joint associations of cardiorespiratory fitness (CRF) and BMI with the incidence of type 2 diabetes in women.RESEARCH DESIGN AND METHODS -An observational cohort of 6,249 women aged 20 -79 years was free of baseline cardiovascular disease, cancer, and diabetes. CRF was measured using a maximal treadmill exercise test. BMI was computed from measured height and weight. The incidence of type 2 diabetes was identified primarily by 1997 Ameri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
152
4
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 159 publications
(169 citation statements)
references
References 39 publications
(61 reference statements)
9
152
4
4
Order By: Relevance
“…Some previous studies concluded that the relative contribution of obesity was more important than physical activity on the risk of type 2 diabetes in women (6,7). However, in our recent study of women using objectively measured fitness instead of self-reported physical activity, obesity and fitness made similar contributions to the risk of type 2 diabetes (15). To date, no study on this issue has been conducted in men.…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…Some previous studies concluded that the relative contribution of obesity was more important than physical activity on the risk of type 2 diabetes in women (6,7). However, in our recent study of women using objectively measured fitness instead of self-reported physical activity, obesity and fitness made similar contributions to the risk of type 2 diabetes (15). To date, no study on this issue has been conducted in men.…”
mentioning
confidence: 55%
“…We created six categories of BMI and fitness combinations and four categories of waist girth or percent body fat and fitness combinations using nonobese and fit men as the referent. In Cox regression models, baseline age, examination year, parental diabetes, current smoking, alcohol consumption, blood pressure, total cholesterol, baseline IFG, BMI, and treadmill time were considered as potential confounders as in previous studies (11)(12)(13)15,23). The proportional hazards assumption was tested by examining the log-log survival plots grouped on exposure categories.…”
Section: Clinical Examinationmentioning
confidence: 99%
“…[16][17][18] We have also shown that both statin therapy and increased cardiorespiratory fitness were independently associated with lower mortality risk in those treated and not treated with statins. 19 Additionally, the combination of statin therapy and increased cardiorespiratory fitness was more effective in lowering mortality risk than either alone.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Epidemiological studies confirm that physical activity like regular exercise is related to the decreased incidence of DMT2 [9][10][11][12]. Also several studies have demonstrated that exercise alone has clinical benefits, such as improving insulin sensitivity, reducing glycated hemoglobin (A1c) and increasing peak oxygen consumption (VO 2 peak) [13][14][15].…”
Section: Introductionmentioning
confidence: 97%